2017
DOI: 10.3892/or.2017.5568
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA MEG3 induces cell apoptosis in esophageal cancer through endoplasmic reticulum stress

Abstract: Long non-coding RNAs (lncRNAs) play important roles in diverse biological processes, such as cell growth, apoptosis and migration. Although downregulation of lncRNA MEG3 has been identified in several cancers, little is known about its role in esophageal squamous cell carcinoma (ESCC). The aim of the present study was to detect MEG3 expression in clinical ESCC tissues, investigate its biological functions and the endoplasmic reticulum (ER) stress-relative mechanism. MEG3 expression levels were detected by qRT-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 25 publications
2
48
0
Order By: Relevance
“…For instance, upregulation of MEG3 inhibited breast cancer cells proliferation and invasion capacities . MEG3 was able to inhibit cell growth and induced apoptosis in esophageal squamous cell carcinoma EC109 cells . However, to our knowledge, there is only one literature reported the functional impacts of MEG3 on OS cells, and in which MEG3 was indicated as a tumor suppressor .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, upregulation of MEG3 inhibited breast cancer cells proliferation and invasion capacities . MEG3 was able to inhibit cell growth and induced apoptosis in esophageal squamous cell carcinoma EC109 cells . However, to our knowledge, there is only one literature reported the functional impacts of MEG3 on OS cells, and in which MEG3 was indicated as a tumor suppressor .…”
Section: Discussionmentioning
confidence: 99%
“…It was previously determined that ERS was prevalent in tumor tissues (25). ERS was positively correlated with the depth of tumor invasion and degree of metastasis, indicating that ERS might be an important inducement of invasion and metastasis of tumor cells (26). ERS, a type of self-protective reaction of the cells, is involved in the occurrence and development of breast, liver and pancreatic cancer (27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
“…36 Moreover, it has been shown that MEG3 inhibits cell growth and induces apoptosis in ESCC cells, mostly via activation of the endoplasmic reticulum stress pathway. 50 Furthermore, Zhang et al reported that MEG3 suppresses BC cell growth, invasion, and tumor angiogenesis via downregulation of AKT signaling pathway, and hence may serve as a novel therapeutic target of BC. 52 Consistent with these findings, Braconi and colleagues have reported that aberrant expression of MEG3 may F I G U R E 3 A, Forest plot demonstrating subgroup analysis of the relationship between MEG3 expression with OS in patients with GI; or B, breast cancer.…”
Section: Discussionmentioning
confidence: 99%